EFFECTS OF PACKAGING MEFFECTS OF HERMETIC AND NON-HERMETIC PACKAGING MATERIALS ON THE PROXIMATE, FUNCTIONAL AND PASTING PROPERTIES OF FERMENTED CASSAVA FLOUR (LAFUN) DURING 6-MONTH STORAGEATERIALS ON THE PROXIMATE, FUNCTIONAL AND PASTING ATTRIBUTES OF STORED FERMENTED CASSAVA FLOUR (LAFUN) - Popoola, Samuel Taiwo; Balogun, Bukky; Adeniyi, Boluwaji Matthew; Ilori, A.O.; Ajisafe, Segun; Odeniyi, Toluwalope Adewale; Solomon-Ibuwunwa, Oluwakemi Mobolade; Ajala, Odunola Victoria; Oyelakin, M.O. (FUDMA Journal of Sciences, 2025)
This research evaluated the effects of packaging materials on the proximate, functional, and pasting attributes of fermented cassava flour (Lafun) in storage. The study involved the storage of cassava flour in PICS bag, plastic container and polypropylene bag for six (6) months. The proximate attributes of cassava flour stored in the three packaging materials showed a significant decrease in ash content, crude fibre, and crude protein. In comparison, a significant increase was observed in moisture content and carbohydrates in cassava flour stored in the different packaging materials upon completion of the study. The results from the functional properties indicate a significant decrease in the swelling capacity, oil absorption capacity, water absorption capacity and bulk density of cassava flour stored in PICS bags, plastic containers and polypropylene bags, respectively. Results of the pasting properties also indicate that peak viscosity, trough viscosity and breakdown viscosity of cassava flour stored in the polypropylene bag decrease significantly, while a significant increase was observed in the pasting temperature of flour stored in a plastic container and PPICS bag. In conclusion, PPICS bags serve as a better packaging material for fermented cassava flour than plastic containers and polypropylene bags.